Combination of alcohol and glucose consumption as a risk to induce reactive hypoglycemia. Issue 4 (7th September 2020) - Oba‐Yamamoto, Chiho; Takeuchi, Jun; Nakamura, Akinobu; Takikawa, Ryoko; Ozaki, Ayano; Nomoto, Hiroshi; Kameda, Hiraku; Cho, Kyu Yong; Atsumi, Tatsuya; Miyoshi, Hideaki
Abstract: Aims/Introduction: Alcohol consumption has been reported to cause hypoglycemia. However, the mechanism involved has not been unequivocally established. This study comprised healthy volunteers. We carried out a prospective trial to compare the effects of glucose and alcohol consumption, alone or in combination, on glucose and lipid metabolism. Materials and Methods: A 75‐g oral glucose tolerance test (OGTT), a combined 75‐g glucose plus 20‐g alcohol tolerance test (OGATT) and a 20‐g alcohol tolerance test (OATT) were carried out in the participants. Plasma glucose, insulin, triglyceride and ethanol concentrations during each test were compared. Results: We studied 10 participants. Their plasma glucose concentrations 15 and 30 min after the intake of 75 g of glucose were significantly higher during the OGATT than the OGTT. Hypoglycemia occurred in five participants after the OGATT, which was significantly more frequently than after the OGTT ( P  = 0.046). Hypoglycemia did not occur after the OATT, and the ethanol concentration was significantly lower after the OGATT than the OATT. The changes in triglyceride concentration from 30 min after the consumption of 75 g of glucose were significantly greater during the OGATT than the OGTT. The plasma insulin concentrations peaked after 60 min during both the OGTT and OGATT, and were significantly higher during the OGATT ( P  = 0.047). There were no differences between the two interventions in the Matsuda or disposition indexes. Conclusions: Hypoglycemia occurred more frequently after the simultaneous consumption of alcohol plus glucose than after the consumption of glucose alone, suggesting that alcohol in the combination of glucose induces reactive hypoglycemia. Abstract : Hypoglycemia occurred more frequently following the simultaneous ingestion of alcohol plus glucose than following the ingestion of glucose alone, suggesting that alcohol in the combination of glucose induces reactive hypoglycemia.